Bank Risk Aversion and the Risk-Taking Channel of Monetary Policy in the Euro Area - Dajcman, Silvo (Panoeconomicus, 2017)
The financial crisis has provoked economic policy interest and academic research on the functioning and empirical verification of the risk-taking channel of monetary policy. The results of this paper demonstrate how the European Central Bank’s Bank Lending Survey responses can be used to construct a "pure" risk aversion indicator of banks’ business lending. Using panel vector autoregression econometric methodology, we find evidence that the monetary policy affects the "pure" risk aversion of banks and later affects business loans and inflation in the euro area. The results suggest that the risk-taking channel in the euro area is operational.Key words: Bank credit standards, Monetary policy, Risk-taking channel of monetary policy transmission.JEL: E44, E51, G21.Finansijska kriza izazvala je interesovanje ekonomske politike i naučna istraživanja o funkcionisanju i empirijskoj verifikaciji kanala za preuzimanje rizika monetarne politike. Rezultati ovog rada pokazuju kako se odgovori ankete o kreditiranju banaka Evropske Centralne Banke mogu koristiti za konstrukciju “čistog” indikatora averzije rizika kreditiranja poslovanja privrednih banaka. Koristeći ekonometrijsku metodologiju autoregresivnog vektorskog modela dolazimo do dokaza da monetarna politika utiče na “čistu” averziju rizika banaka, a kasnije utiče na poslovne kredite i inflaciju u eurozoni. Rezultati ukazuju na to da je kanal za preuzimanje rizika u eurozoni operativan.Ključne reči: Bankarski kreditni standardi, Monetarna politika, Kanal preuzimanja rizika monetarne politike.